Reactive heavy metals govern soil microbial communities: Depth-resolved evidence and disentangled metal-specific effects - Lixue Qiu; Chenle Wang; Fuxing Wu; Yueming Han; Lixun Zhang (Journal of Hazardous Materials, 2026)

Insight into the pollution potential of different ecological types of lakes from the perspective of dissolved organic matter characteristics: Field and experimental evidence - Yang Deng; Longmian Wang; Yueming Zhu; Xiang Zhu; Qingqing Pang; Yuying Ma; Fuquan Peng; Lei Xie; Xiaoguang Xu; Qiu Jin; Guoxiang Wang; Fei Yang; et al. (Journal of Hydrology, 2025)

Conditional generative adversarial network (cGAN) for generating building load profiles with photovoltaics and electric vehicles - Yuewei Li; Bing Dong; Yueming Qiu (Energy and Buildings, 2025)

What drives embodied carbon policy? A global perspective on adoption - Ming Hu; Yueming Qiu; Ali Nouri (Environment, Development and Sustainability, 2025)
Embodied carbon refers to the greenhouse gas emission associated with the lifecycle of buildings. Embodied carbon policies are critical for addressing the environmental impact of construction materials and advancing climate goals. Despite their importance, the adoption of embodied carbon policies has been limited globally, influenced by economic, environmental, institutional, and trade factors. This study employs structural equation modeling to analyze 37 countries, testing ten hypotheses across four categorical factors. The base model reveals the significant influence of environmental vulnerability and institutional frameworks on policy adoption, while robustness models confirm the critical role of trade dependencies and economic competitiveness in shaping national embodied carbon strategies. Findings underscore that countries with high climate vulnerability and strong institutional support are more likely to adopt embodied carbon policies. Conversely, trade-reliant nations face challenges balancing competitiveness and sustainability. Policy implications suggest the need for international collaboration to align trade policies with carbon reduction goals, targeted support for vulnerable nations, and the integration of embodied carbon considerations into existing climate frameworks. These results offer a roadmap for policymakers to design more effective and equitable embodied carbon policies, fostering global progress toward sustainable construction and decarbonization.

Freezing or searing: Unraveling the impact of extreme temperatures on poverty in China - Huiming Zhang; Shuyuan Wang; Kai Wu; Yueming (Lucy) Qiu; Shouyang Wang; Yongfan Zhao (Environmental Impact Assessment Review, 2025)

The unequal impacts of extremely high temperatures on households’ adaptive behaviors: Empirical evidence from fine-grained electricity consumption data - Han Shi; Bo Wang; Yueming Lucy Qiu; Nana Deng; Baichen Xie; Bin Zhang; Shijun Ma (Energy Policy, 2024)

Liraglutide attenuates palmitate-induced apoptosis via PKA/β-catenin/Bcl-2/Bax pathway in MC3T3-E1 cells - Lanlan Cheng; Yijing Xu; Yueming Long; Fangmei Yu; Li Gui; Qiu Zhang; Yunxia Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Forgone summertime comfort as a function of avoided electricity use - Minji Kwon; Shuchen Cong; Destenie Nock; Luling Huang; Yueming (Lucy) Qiu; Bo Xing (Energy Policy, 2023)

Climate change impacts on future residential electricity consumption and energy burden: A case study in Phoenix, Arizona - Andrew Jones; Destenie Nock; Constantine Samaras; Yueming (Lucy) Qiu; Bo Xing (Energy Policy, 2023)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Inequalities across cooling and heating in households: Energy equity gaps - Luling Huang; Destenie Nock; Shuchen Cong; Yueming (Lucy) Qiu (Energy Policy, 2023)

The impact of co-adopting electric vehicles, solar photovoltaics, and battery storage on electricity consumption patterns: Empirical evidence from Arizona - Xingchi Shen; Yueming Lucy Qiu; Xing Bo; Anand Patwardhan; Nathan Hultman; Bing Dong (Resources, Conservation and Recycling, 2023)

Increasing voluntary enrollment in time-of-use electricity rates: Findings from a survey experiment - Corey Lang; Yueming (Lucy) Qiu; Luran Dong (Energy Policy, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

A comparison of building energy codes and policies in the USA, Germany, and China: progress toward the net-zero building goal in three countries - Ming Hu; Yueming Qiu (Clean Technologies and Environmental Policy, 2019)